The Effect of Growth Regulator Substance in Cultural Media PHM on Protein Content of Chlorella sp. - Lewaru, M.W. (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
In developing fish cultivation, it is better to make an effort to support a sustainable larva availability with the high quality and quantity. This is due that the larva stadium is a susceptible phase and the most critical condition in a whole fish life cycle. Hence, in obtaining a life cycle sequence and high quality of the fish, the most important thing to do is providing natural foods of the fish. One of them is Chlorella sp, this species has the size which is suitable to the orifice of the larva and it contains high nutrient such as protein. This research aims to investigate the effect of adding a growth regulator substance in cultural PHM media on the protein content of Chlorella sp. The method used in this research was experimental laboratory using a completely random design which comprised of five treatments with triplicates per treatment. Treatments A (PHM + PSB 0.005 mL/L), B (PHM + PSB 0.01 mL/L), C (PHM + PSB 0.015 mL/L), D (PHM + PSB 0.02 mL/L), and K (PHM without PSB). Parameters observed and analysed were growth and protein content of Chlorella sp. During the study, parameters of the water quality measured were temperature (0C), pH, ammoniak, nitrit, and nitrat. The results of the study showed that adding a growth regulator Penshibao (PSB) in the media with various doses gave significant effects (P